The Tree that Therefore I am - Joshua Reno (Semiotic Review)
Post Tenebras Lux is the critically-acclaimed, fourth film by Mexican filmmaker Carlos Reygadas: semi-autobiographical yet surreal; global yet Mexican; a simple drama about two married couples and an experimental study in interspecies desire and mimesis. The last is the focus of this paper. Like the documentary Leviathan, released the same year, Post Tenebras Lux can be regarded as a contribution to multispecies ethnography and ontological theorizing. In this paper, the film is interpreted as a meditation on distinctly vegetative semiosis and becomings-plant, as well as the possibilities and politics thereof.